The Development of Comparing Academic Achievement History Course of Mathayom 4 Students at Suankularb Wittayalai Saraburi School using Multimedia and Traditional Learning - Kingkan, Pimpaka; Limtasiri, Oranuch (Academic MCU Buriram Journal, 2024)
The purposes of this research were: 1) create and find the efficiency of multimedia according to the 80/80 criteria. 2) compare academic achievement History subject before and after using multimedia. 3) compare academic achievement History course between before and after using traditional learning management and 4) compare academic achievement History course using multimedia and traditional learning management. The population was Mathayom 4. Province Under the Saraburi Secondary Educational Service Area Office, 250 people. Purposive samplings included 34 students in Mathayom 404 (room 4) for experimentation and 34 students in Mathayom 407 (room 7) for control group. The tools used in the research were 1) multimedia learning media for the history subject 2) learning management plans for the history subject using multimedia 3) learning management plans for the history subject using traditional learning management 4) Achievement test for history subjects. The reliability of the whole test was 0.96. Results were analyzed using mean, percentage, and standard deviation. E1 / E2 T-test. The research result found that: 1. multimedia History course For Mathayom 4 students, the efficiency value was 82.67/83.50, which met the criteria of 80/80. 2. Academic achievement in history subjects the average score after studying with multimedia management was higher than the score of studying with traditional management. Statistically significant at the .05 level. 3. Academic achievement in history subjects of Mathayom 4 students who received learning management using normal learning management after learning was higher than before learning. Statistically significant at the .05 level. 4. Academic achievement in history subjects. of Mathayom 4 students who received learning management using multimedia media was higher than that of normal learning management. Statistically significant at the .05 level.